Shrinkage Estimators for Reliability Function - Mohammad Qabaha (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
A variety of shrinkage methods for estimating unknown parameters has been considered. We derive and compare the shrinkage estimators for the reliability function of the two-parameter exponential distribution. Simulation experiments are used to study the performances of these estimators.